The Effect of Issuer Conservatism on IPO Pricing and Performance* - Ferris, Stephen P.; Hao, (Grace) Qing; Liao, (Stella) Min-Yu (Review of Finance, 2013)
Based on a textual analysis of initial public offering (IPO) prospectuses, we obtain a number of important findings regarding the relation between the conservatism in prospectuses, IPO pricing, and subsequent operating and stock return performance. First, prospectus conservatism is positively related to underpricing, with the relation more pronounced for technology than nontechnology firms. Second, for nontechnology IPOs, prospectus conservatism is able to predict the firm’s post-IPO operating performance. Specifically, we find that conservatism is inversely related to the firm’s operating performance for the 3 years following the IPO. However, this predictability is limited to nontechnology IPOs. Finally, we find some evidence that for nontechnology IPOs conservatism is inversely related to the firm’s post-IPO abnormal stock return. We conclude that the conservatism contained in an IPO’s prospectus contains useful information about pricing and subsequent operating and stock return performance. Moreover, prospectus conservatism for nontechnology IPOs deserves more attention from investors.